Effect of undernutrition on cranial components and somatotroph-lactotroph pituitary populations in the squirrel monkey (Saimiri sciureus boliviensis) - Console de Avegliano, Gloria Miriam (2001)
The aim of the present study was to investigate in monkeys the effects of undernutrition on neurocranial and facial components, correlated with a histometric and ultrastructural analysis of somatotroph (growth hormone, GH) and lactotroph (prolactin, PRL) pituitary populations. Twenty Saimiri sciureus boliviensis (Cebidae) of both sexes were employed. The monkeys were born in captivity and when they reached 1 year of age, they were separated into two groups: control and undernourished animals. They were fed ad libitum a 20% and 10% protein diet, respectively. The monkeys were radiographed when they were 3 years old in order to measure the length, width and height of the anterior, middle and posterior components of the neurocranium, as well as those of the masticatory, respiratory and optic components of the face. The volumetric and morphometric indices were then calculated. After the sacrifice, pituitary glands were processed for light and electron microscopy. The quantitative immunohistochemistry revealed a decrease in the volume density and cell density of both GH and PRL cells from malnourished animals when compared to control ones. The ultrastructural study showed changes suggestive of cellular hyperfunction for both types of cells in the former experimental group. Undernutrition also affected the size of the cranial components, with males being more affected than females; brain weight was, however, nonmodified by stress, with the brain/body ratio difference being the same for both sexes. We conclude that in monkeys, experimental undernutrition produces a decrease in the pituitary GH and PRL cell populations, in some way related to changes in the cranio-facial morphometric patterns.